Increase Profitability through the Company’s Internal Factors: A Study in West Java, Indonesia - Ligar Hardika, Andhika; Nur Fathonah, Andina; Darrini, Anni; Larasati Agustina, Inggrid (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze loan to deposit ratio, operational efficiency and firm size and return on equity of the companies in West Java, Indonesia. This type of research uses descriptive verification. The population is a bank registered on the Indonesian stock exchange and sampling uses purposive sampling. This research has tested the classical assumptions and then processed using Eviews 10. This study found that loan to deposit ratio, operational efficiency and firm size loan to deposit ratio, operational efficiency and firm size affects the return on equity (ROE). This research provides insight to investors in investing funds or investing in banks that need to pay attention to information about the loan to deposit ratio, operational efficiency, and firm size because it can also increase income so that reciprocity to investors will be good and beneficial.